A Stochastic Model of Indigenous Language Extinction in Nigeria - Ikoba, N.A.; Jolayemi, E.T. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2016)
The need to effectively capture indigenous language decline is explored in this study. Language decline was conceptualized as a Poisson process in order to study the dynamics. Expressions and estimates were derived for the intergenerational transmission probability, the probability of eventual extinction and the mean number of transfers per family. For model validation, a household survey was conducted in Salem City, Warri, Nigeria. Demographic information about the community was elicited through a multi-dimensional questionnaire, which also provided information on the actual number of children who were able to imbibe their heritage language, across two generations. A massive demographic shift was observed in the family sizes over the two generations studied. There was also a general decline in intergenerational transmission, pointing to the possible extinction of such languages in generations to come. Our study also showed that a great proportion of parents in the sampled community have indigenous language ability but hardly impart such to their offspring. The findings further indicated that some indigenous languages are under serious threat of extinction if conscious steps are not taken to arrest the decline. This model can be used to ascertain the status of any indigenous language globally